Recollection and Taxonomic Placement of Alpinia apoensis (Zingiberaceae; Alpinioideae): An Imperfectly Known Philippine Endemic Species - Mark Arcebal Kling Naive; Jade Ann Grace Dalisay; Porferio Bangcaya; Grecebio Jonathan Duran Alejandro (Journal of Tropical Life Science, 2019)
A recent exploration on the Mt. Kalatungan Range Natural Park of Bukidnon and Mt. Madjaas of Antique resulted in the recollection of Alpinia apoensis. It is an endemic Zingiberaceae species of uncertain identity that was first collected and described by Elmer over 90 years ago. As there is no comprehensive revision of the family Zingiberaceae in the Philippines, it is meanwhile important to clarify its taxonomic identity. This study contributes a comprehensive description of the species leading to the determination of its sectional and subsectional placements. Information on its geographical distribution, phenology, ecology, and coloured photographs are also provided.